Notch Signaling Pathway Regulates Angiogenesis via Endothelial Cell in 3D Co‐Culture Model. Issue 6 (20th November 2016) - Zhao, Dan; Xue, Changyue; Lin, Shiyu; Shi, Sirong; Li, Qianshun; Liu, Mengting; Cai, Xiaoxiao; Lin, Yunfeng
Abstract : This study aimed to investigate the role of Notch signaling pathway for angiogenesis in a three‐dimensional (3D) collagen gel model with co‐culture of adipose‐derived stromal cells (ASCs) and endothelial cells (ECs). A 3D collagen gel model was established in vitro by implanting both ASCs from green fluorescent protein‐labeled mouse and ECs from red fluorescent protein‐labeled mouse, and the phenomena of angiogenesis with Notch signaling inducer Jagged1, inhibitor DAPT and PBS, respectively were observed by confocal laser scanning microscopy. Semi‐quantitative PCR and immunofluorescent staining were conducted to detect expressions of angiogenesis‐related genes and proteins. Angiogenesis in the co‐culture gels was promoted by Jagged1 treatment while attenuated by DAPT treatment, compared to control group. In co‐culture system of ASCs and ECs, the gene expressions of VEGFA, VEGFB, Notch1, Notch2, Hes1, Hey1, VEGFR1, and the protein expression of VEGFA, VEGFB, Notch1, Hes1, Hey1 were increased by Jagged1 treatment and decreased by DAPT treatment in ECs. And the result of VEGFR3 was the opposite. However, the same results did not appear completely in ASCs. These results revealed the VEGFA/B‐Notch1/2‐Hes1/Hey1‐ VEGFR1/3 signal axis played an important role in angiogenesis when ASCs and ECs were co‐cultured in a 3D collagen gel model. J. Cell. Physiol. 232: 1548–1558, 2017. © 2016 Wiley Periodicals, Inc. Abstract : VEGFA/B‐Notch1/2‐Hes1/Hey1‐ VEGFR1/3 signal axis played an important role in angiogenesis when ASCs and ECs were co‐cultured in a 3D collagen gel model.